Are There any Differences Between Muslim and Non-Muslim Countries in Terms of Income Inequality? - CAVUSOGLU, Behiye (Journal of Advanced Research in Law and Economics, 2017)
Income inequality is one of the most important problems in today’s world. It has many negative effects on both social and economic environment, which need to be eliminated. The study aims to analyze the positive and negative effects of religion and the Islam on economy. The study also tried to find an answer to the question ‘if the economic inequalities are affected by religion; are religious countries more equal?’ Previous researches proved that there is a correlation between religion and economy. The Islam has many positive effects on economy, as it has the idea of working as worship and being honest while working and also it has many negative effects as the commodity is not valued in the religion. The paper also aimed to investigate if there is a difference between the Muslim countries and the others in the case of economic inequality. It is hard to clarify if the Muslim countries are different than other countries in the sense of economic inequality